Biological Control of Pest and Vector Insects - Shields, Vonnie D.C (IntechOpen, 2017)
This book provides recent contributions of current strategies to control insect pests written by experts in their respective fields. Topics include semiochemicals based insect management techniques, assessment of lethal dose/concentrations, strategies for efficient biological control practices, bioinsecticidal formulations and mechanisms of action involving RNAi technology, light-trap collection of insects, the use of sex pheromonal components and attractants for pest insect capture, measures to increase plant resistance in forest plantations, the use of various baculoviruses as biopesticides, and effect of a pathogenic bacterium against an endangered butterfly species. There are several other chapters that focus on insect vectors, including biting midges as livestock vectors in Tunisia, mosquitoes as vectors in Brazil, human disease vectors in Tanzania, pathogenic livestock and human vectors in Africa, insect vectors of Chagas disease, and transgenic and paratransgenic biotechnologies against dipteran pests and vectors. This book targets general biologists, entomologists, ecologists, zoologists, virologists, and epidemiologists, including both teachers and students.